Technological change and tropical deforestation: a perspective at the household level - Soest, D.P. van; Bulte, E.H.; Angelsen, A.; Kooten, G.C. van (2002)
This paper analysis the effects of technological change in agriculture on forest clearing by households in developing countries. The possible effects are found to be many and diverse, depending on the type of change and the institutional context. It concludes that agricultural intensification is certainly not the panacea that some believe it to be.